Presence of oestrogen receptor type β in human retina. Issue 7 (1st July 2001) - Munaut, Carine; Lambert, Vincent; Noël, Agnès; Frankenne, Francis; Deprez, Manuel; Foidart, Jean-Michel; Rakic, Jean-Marie
Abstract : BACKGROUND/AIMS: Recent studies have demonstrated the existence of two oestrogen receptor subtypes α (ORα) and β (ORβ) with significant differences of expression among organs. Since important pathologies of human eye could be linked to hormonal status, the expression of ORβ in ocular posterior segment was sought. METHODS: Immunohistochemical localisation of ORβ and ORα protein and detection of OR mRNAs by reverse transcription-polymerase chain reaction (RT-PCR) were performed in macular and extramacular regions of the retina and in the choroid on male and female donors eyes. RESULTS: ORβ protein was localised in the ganglion cell layer and in the choroid. At the transcriptional level, mRNA for ORβ and for ORα were both present. Local differences in the expression level were observed, however, suggesting the possibility of variation in the ratio of ORα v ORβ. CONCLUSIONS: The coexistence of two oestrogen receptor subtypes in the human ocular posterior segment raises acute questions about their potential physiological role, but offers a perspective for preferential targeting of a specific receptor subtype.